An exploratory investigation of traditional scoring in diving and relationships to the development of Artificial Intelligence opportunities - Jakab, S.; Davis, P.; Whyte, I. (Scientific Journal of Sport and Performance, 2023)
This study investigated the conceptions of perfection that figure in the minds of divers, coaches, and judges. Additionally, consideration was given to their views of whether an Artificial Intelligence (AI) based scoring system could be relied upon to yield authentic results, allied with the desirability of its use. Six participants (2 each of diver, coach, judge) were interviewed. Following verbatim transcriptions, thematic analyses were conducted to identify commonly occurring themes relevant to diving and its scoring system. The results of this preliminary study have shown a leaning towards clarification of the rules on point deductions by FINA (Fédération Internationale De Natation/ International Swimming Federation). Furthermore, the concept of perfection in diving changes from country to country and culture to culture, providing further difficulties in the objectivity of judging and there was a call for openness and clarity. With the human element of judging carrying weakness and allowing for errors, subsequently, it was felt by the respondents that some parts of a dive should be measured with technology where feasible. There was a consensus that judges could not be fully replaced without substantive changes to the sport of diving, in effect losing the artistic element that is subjectively assessed.